Grounds of Natural Philosophy: Divided into Thirteen Parts : The Second Edition, much altered from the First, which went under the Name of Philosophical and Physical Opinions - Newcastle, Margaret Cavendish, Duchess of, 1624?-1674 (Salt Lake City, UT : Project Gutenberg, 2018)
"Grounds of Natural Philosophy: Divided into Thirteen Parts" by Newcastle is a foundational work in natural philosophy written in the late 17th century. The text explores the nature of matter, motion, perception, and life, presenting the author$1 (Bs contemplations and arguments about the physical world based on the self-moving parts of nature. It delves into various philosophical inquiries surrounding the essence of existence and the interplay between different forms of matter and motion. The opening of the text begins with an appeal to European universities, where the author, Margaret Newcastle, expresses her desire for critical examination of her ideas despite her self-professed lack of formal training. She acknowledges the imperfections in the first edition of her work and hints at the corrections made in this second edition. The initial chapters introduce fundamental concepts such as matter$1 (Bs definitions, the relationship between motion and matter, and the necessity of a unified understanding of nature$1 (Bs properties, laying the groundwork for her more complex explorations into perception, life, and the characteristics of various beings. (This is an automatically generated summary.)s
Release date is 2018-12-03
Produced by Marc D'Hooghe at Free Literature
Keywords: Physics -- Early works to 1800